Représentations de l’absence et du manque : de La Dispersion au Livre brisé de Serge Doubrovsky - Levy, Nurit (Quêtes littéraires, 2011)
Author and academic, Serge Doubrovsky is an important figure in contemporary French literature. His numerous publications foretell the emergence of a new literary concept, positioning him in the domain of post-modernism with the emergence of auto-fiction. From The Dispersion to The Broken Book, the auto-fiction unfolds in a jerky narrative while the genesis of the work revolves around a profound sense of lack and absence that the writer tries to fill through his writing. The experience of World War II left a life long indelible mark on the writer’s own identity and brings forth the creation of this hybrid autobiography that aims at tearing down ge-neric and literary boundaries. Letters and words are used to confront what is missing in his life in a transgressing style that describes the violence of this experience. In this way, Doubrovsky leaves a trace of his existence, transforming his life into a novel – a work of fiction – and by giving space to imagination when telling his own story.